Self-Efficacy and Compliance Fluid Intake Restrictions in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Cross-Sectional Study - Fitri Mailani; Mahathir Mahathir; Annisa Rahma Yuni (STIKep PPNI Jawa Barat, 2023)
Aims: Good self-efficacy will encourage patients to behave assertively and adhere to medication, diet, and fluid restrictions in patients with chronic kidney disease undergoing hemodialysis. However, nowadays, patient non-compliance with fluid restrictions is still high, which results in increased complications experienced by patients. The study aimed to determine the relationship between self-efficacy and adherence to fluid intake restrictions in chronic kidney patients undergoing hemodialysis at RSUP Dr. M. Djamil Padang. Methods: This study used a correlation study design and a cross-sectional method. The total sample was 81 respondents. Using purposive sampling with inclusion criteria, patients routinely undergo HD > 3 months, are over 18 years old, and can communicate well. The instruments used were the Self-Efficacy for Managing Chronic Disease (SEMCD) questionnaire and the Fluid Intake Restriction Adherence questionnaire—data analysis using the Spearman correlation test. Result: The results revealed a significant relationship between self-efficacy and adherence to fluid intake restrictions (p = <0.001) with a value (r = 0.703) which means the correlation for both variables is firmly in positive relation. Conclusion: Nurses in the HD room are expected to be able to provide self-efficacy training to patients to increase patient compliance, the higher the self-efficacy, the more compliant the patient with fluid intake restrictions. Keywords: Adherence, Fluid, Hemodialysis, Self-Efficacy.